The Role of Neurolinguistics in Teaching Greek as a Second Language:: A Comprehensive Review - Moumouri, Amalia; Katerelos, Adamantios (International Journal of Language Teaching and Education, 2025)
Neurolinguistics provides crucial insights into the cognitive and neural mechanisms underlying second language acquisition, offering fertile ground for improving the teaching of Greek as a second language (L2). This article presents a comprehensive review of research at the intersection of neurolinguistics and Greek language pedagogy. It discusses findings on cognitive processing, phonological and grammatical challenges, multisensory learning, affective dimensions such as motivation and anxiety reduction, and dynamic assessment methods. Special attention is given to technological innovations, pragmatic competence, and cultural immersion. The review also critically evaluates current research gaps, emphasizing the need for empirical studies specifically on Greek L2 acquisition. By integrating cognitive science, pedagogy, and sociocultural approaches, the article proposes evidence-based directions for teaching methodologies that foster both linguistic competence and cultural integration